2014
DOI: 10.1159/000358653
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of TRPV6 Causes Osteopenia in Mice by Increasing Osteoclastic Differentiation and Activity

Abstract: Background: Calcium ion (Ca2+) signals are required for osteoclast differentiation. Previous study showed that transient receptor potential vanilloid 5 (TRPV5) is an essential Ca2+ transporter in osteoclastogenesis and bone resorption. TRPV5 and TRPV6 represent two highly homologous members within the transient receptor potential (TRP) superfamily. However, the role of TRPV6 in bone metabolism is still controversial and little is known about the involvement of TRPV6 in receptor activator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…The low endolymphatic pH in Pendrin-deficient mice appears to inhibit acid-sensitive TRPV5/6 calcium channels, increasing endolymphatic calcium that likely contributes to the formation of abnormal otoconia crystals (Nakaya et al, 2007). TRPV4 knockout mice have hearing defects, and both TRPV5 and TRPV6 mouse knockouts as well as a trpv6 mutant zebrafish have defective bone formation (Chen et al, 2014; Hoenderop et al, 2003; Tabuchi et al, 2005; Vanoevelen et al, 2011). However, TRPV-deficient mice and zebrafish have not been associated with significant otoconia/otolith abnormalities.…”
Section: Direct Regulators Of Otoconia and Otolith Developmentmentioning
confidence: 99%
“…The low endolymphatic pH in Pendrin-deficient mice appears to inhibit acid-sensitive TRPV5/6 calcium channels, increasing endolymphatic calcium that likely contributes to the formation of abnormal otoconia crystals (Nakaya et al, 2007). TRPV4 knockout mice have hearing defects, and both TRPV5 and TRPV6 mouse knockouts as well as a trpv6 mutant zebrafish have defective bone formation (Chen et al, 2014; Hoenderop et al, 2003; Tabuchi et al, 2005; Vanoevelen et al, 2011). However, TRPV-deficient mice and zebrafish have not been associated with significant otoconia/otolith abnormalities.…”
Section: Direct Regulators Of Otoconia and Otolith Developmentmentioning
confidence: 99%
“…Although many systemic hormones and local cytokines participate in regulating osteoclast differentiation (osteoclastogenesis), the receptor activator of NF-κB (RANK) ligand (RANKL) is the most critical molecular for osteoclastogenesis in cooperation with macrophage colony-stimulating factor (M-CSF) in the interaction between stromal cells and cells of the OCs lineage [2, 3]. Binding of RANKL to cell surface receptor RANK sequentially activate downstream signaling molecules including: the nuclear factor-κB (NF-κB) and mitogen activated protein kinases (MAPKs) [4].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that differentiation and activation of osteoclasts at the [2,32]. Among cytokines that demonstrate multi-effect in spurring excessive osteoclast activity and promoting osteolytic metastasis, RANKL is the most prominent cytokine inducer of osteoclastogenesis [1,33,34]. RANKL binding to its receptor (RANK) expressed on the osteoclast precursors and metastatic cells activates NF-κB signaling, resulting in both the transcription of crucial osteoclastogenic cytokines and elevated breast cancer cell migration selectively to bone [2].…”
Section: Discussionmentioning
confidence: 98%